Perspectives and Challenges for Sustainable Management of Fungal Diseases of Mungbean [Vigna radiata (L.) R. Wilczek var. radiata]: A Review - Pandey, Abhay K.; Burlakoti, Rishi R.; Kenyon, Lawrence; Nair, Ramakrishnan M. (Frontiers in Environmental Science, 2018)
Mungbean (Vigna radiata var. radiata) is a key legume crop grown predominantly in South and Southeast Asia. Biotic and abiotic stresses cause significant yield reduction in mungbean, and among these, fungal diseases are particularly important. Although disease management practices, including physical, chemical, and biological methods have been researched and described in the literature, few of these are available or have been used by growers. Here we review the economic impact, pathogen characterization, and sustainable management options for the soil-borne and foliar fungal diseases of mungbean as well as major challenges to manage these diseases. Potential use of all possible components of integrated management practices including host resistance, fungicides, biocontrol agents, natural plant products, and cultural practices etc. are discussed. Major diseases include powdery mildew, anthracnose, Cercospora leaf spot, Fusarium wilt, Rhizoctonia root rot and web blight, Macrophomina charcoal rot/dry root rot and blight. Review of the literature indicated an absence of resistance to Rhizoctonia root rot, little sources of resistance for dry root rot and anthracnose. Major resistant genes (R genes) and quantitative trait loci (QTL) were identified for powdery mildew and Cercospora leaf spot, which may be potentially used in Marker assisted selection (MAS). has been used in resistance breeding for both of the latter. Although the mechanisms of induced systemic resistance (ISR) by biocontrol agents have been studied with Macrophomina blight, there is little information on the mechanisms and use of systemic acquired resistance (SAR) in managing fungal diseases of mungbean. Several studies targeted exploiting biological control for soil-borne root rot diseases. Botanical products, such as plant extracts, are also found effective to manage root and foliar diseases. However, many of these studies were limited to laboratory and/or green house experiments. Thus, long-term field studies are required for further exploitation of biological methods and commercial applications.